J integral computation and Limit load analysis of bonded composite repair in cracked pipes under pressure (Fracture and Structural Integrity, 2019)
In this paper, an additional criterion was introduced to evaluate the composite repair systems using the limit load analysis. The plastic collapse pressure of API 5L X65 PSL2 steel pressure vessel structure with crack defect is numerically investigated after the structure was been repaired by composite overwrap. The objective of this study was the analysis of the efficiency of composite repair systems using this additional criterion to gain more confidence on it taking into account, the cracks and the overwrap geometries. The material of the pipe is elastic perfectly plastic for the plastic collapse pressure criterion and elastic-plastic using the Romberg Osgood model for fracture mechanic criterion. The additional criterion allows us to compare the uncracked and cracked pipe to estimate the repair efficiency. Moreover, the composite overwrap could restore 90% of the plastic collapse pressure for cracked pipes.
Keywords: J integral; API 5L X65; Limit load; Romberg Osgood model; crack; pipe